SCIENCE LITERACY: THE POINT OF VIEW OF STUDENT INTO UNDERSTANDING THE INTERNAL ANATOMY OF SELECTED VERTEBRATES - Bartoszeck, Amauri Betini; Kruszielski, Leandro; Bartoszeck, Flavio Kulevicz (EDUCERE - Revista da Educação da UNIPAR, 2012)
How do people develop understandings of what is inside certain vertebrates including themselves? This study based on a quantitative investigation looks at students’ understandings of internal structures of a rat, a fish, a bird and themselves. A cross-sectional approach was used involving a total of 696 students in southern Brazil from seven different age groups (ranging from four years old to first year Biology undergraduates). Students were asked to draw what they thought were inside the specimens above. Data analysis was carried out following a scoring protocol and entered into SPSS. Gender differences were not statistically significant, whoever, it shows the extent to which student understanding increases with age and the degree to which students know more about some organs and organ systems than others. Educational implications and aspects of science literacy are discussed.